Evaluation of Credit Union Legal Entity Regulations In Increasing MSMEs Capital - SETYOWATİ, Endang; KADARNINGSIH, Ana (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
Indonesia is dominated by MSMEs at the micro business level which need assistance, especially in capital. The existence of Credit Unions really helps MSMEs, especially in providing capital. Until now, Credit Unions are still subject to Law Number 25 of 1992 concerning Cooperatives. This is because there are no specific regulations governing Credit Unions, so their existence is considered to fall within the criteria for savings and loan cooperatives. The problem in this research is how to evaluate the regulatory position of Credit Union legal entities in increasing MSME capital. Several things that are taken into consideration in the evaluation include the name of the legal entity of the Credit Union in Indonesia, organizational structure, form of savings, activities, educational activities, and capital. This evaluation will formulate new regulations that specifically regulate the position of Credit Union legal entities, so that Credit Unions can be more effective in assisting capital for MSMEs. This research is also expected to find improvements in Credit Union legal entity regulations that are more appropriate for MSMEs in improving the Indonesian economy. This research is descriptive analysis using an empirical normative juridical approach. Primary data through interviews with Credit Union managers, employees of the Cooperative and UMKM Service, savings and loan cooperative employees, banking employees and MSME players. Secondary data was obtained from library materials. Article history: Received 28 July 2023 Revised 10 October 2023 Accepted 14 October 2023 SIMILARITY INDEX = 6.00%